Pengaruh remunerasi, motivasi kerja dan kepuasan kerja terhadap kinerja fakultas ekonomi dan bisnis pada UPN “Veteran” Jawa Timur - Nurhidayah, Siti; Munari, Munari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine and prove the effect of remuneration, work motivation, and job satisfaction on the performance of the Faculty of Economics and Business, of University Pembangunan Nasional "Veteran" East Java. Decent remuneration will have an impact on motivating and providing a level of job satisfaction that will support employee performance, especially in this case lecturers and employees. This study uses quantitative methods with primary data sources or the method of distributing questionnaires directly to respondents. The research sample was taken by random sampling technique and the determination of the sample using the slovin formula. The data analysis technique in this research is using the SPSS software for windows v.25 application software. The results of this study prove that the variables of remuneration, work motivation, and job satisfaction have no significant positive effect on employee performance.